Lawrence Atkinson, sculpture, and vorticist multimediality - Waddell, Nathan (Johns Hopkins University Press, 2016)
This article looks closely at the life and career of the avant-garde sculptor and painter Lawrence Atkinson (1873-1931) as a way to reconsider from a new angle at least three persistent clichés about Vorticism (that it was unmusical, that it was stopped by the First World War, and that its members formed a cohesive ‘group’); to establish more firmly an almost entirely unappreciated trajectory within post-war British sculpture, one running from Atkinson’s early interactions with the British Rhythmists to his encounters with Vorticism and beyond; and to re-examine what Matthew Hofer has called the ‘decidedly radical’ early twentieth-century project of non-institutional education focusing on ‘interdisciplinarity through the interaction of the arts’, a project to which Atkinson made a symbolically important contribution. The article suggests that Atkinson deserves a more visible place in histories of avant-garde, inter-disciplinary artistic instruction, and attempts to reclaim Atkinson as a subject worthy of critical scrutiny by showing his importance as a musician and teacher, roles that shaped and benefited from his career as a sculptor in important ways.